Creating innovators the making of young people who will change the world - Wagner, Tony. (New York Scribner, 2012)
Harvard education expert Tony Wagner explores what parents, teachers, and employers must do to develop the capacities of young people to become innovators. In profiling compelling young American innovators such as Kirk Phelps, product manager for Apple?s first iPhone, and Jodie Wu, who founded a company that builds bicycle-powered maize shellers in Tanzania, Wagner reveals how the adults in their lives nurtured their creativity and sparked their imaginations, while teaching them to learn from failures and persevere. Play, passion, and purpose: These are the forces that drive young innovators.
Includes bibliographical references and index.
Keywords: Education, Secondary--Aims and objectives--United States